The child and adolescent patient’s profiles and usefulness of instant collaborative video consultations of tele-psychiatrists with primary care doctors - Rajendra K Madegowda; P Lakshmi Nirisha; Gajanan Ganapati Sabhahit; Narayana Manjunatha; Channavaeerachari Naveen Kumar; Suresh Bada Math (Industrial Psychiatry Journal)
Background: The Tele-Medicine Center at the National Institute of Mental Health and Neurosciences, Bengaluru, organized module-based capacity-building training courses for in-service primary care doctors (PCDs) with MBBS degree. The objective was to bolster the coverage of the National Mental Health Program services and diminish the treatment gap in the region. As part of this training, an instant collaborative video consultation (i-CVC) module allowed PCDs to engage in live, real-time video consultations with tele-psychiatrists at NIMHANS to discuss their patients’ cases. Approximately 7% of the i-CVC cases focused on child and adolescent psychiatric disorders. Aim: Aim of this study is understand the profiles of child and adolescent patients and usefulness of instant collaborative video consultations of tele-psychiatrists with primary care doctors. Materials and Methods: This study delved into data from 41 children and adolescents’ (aged 10–17 years) i-CVC module case proformas. It examined six predefined learning themes highlighted by PCDs and evaluated patientprofiles, along with diagnostic agreement between PCDs and tele-psychiatrists. Results: Among the 41 patients, there were 19 males (46.3%) and 22 females (53.7%), aged between 10 and 17 years. The study identified six key learning themes: clinical assessment, identification and diagnosis, counseling for children and parents, pharmacotherapy, and legal aspects. Emotional disorders were noted in 12 patients (29.3%), developmental disorders in eight patients (19.5%), psychotic disorders in eight patients (19.5%), and behavioral disorders in three patients (7.3%). Pharmacotherapy was initiated for five patients (12.2%), while 23 patients (56.1%) received counseling, and 13 patients (31.7%) received both treatments. Conclusion: Diagnostic agreement between PCDs and tele-psychiatrists was observed in 25 cases (61%). This study represents the first evaluation of the collaborative i-CVC module aimed at training PCDs in child and adolescent psychiatry in India. The 61% diagnostic agreement suggests the feasibility of PCD training. These findings underscore the pressing need for an Indianized, point-of-care manual in child and adolescent psychiatry to train PCDs throughout India.